2021
DOI: 10.3389/fonc.2020.599363
|View full text |Cite
|
Sign up to set email alerts
|

Serum Chemokine CXCL7 as a Potential Novel Biomarker for Obstructive Colorectal Cancer

Abstract: Due to the lack of typical symptoms and signs and sensitive indicators for early diagnosis of obstructive colorectal cancer (OCRC), it is critically needed to find new novel biomarkers to ameliorate the management of OCRC patients. In this study, 472 blood samples were collected and measured by enzyme-linked immunosorbent assay (ELISA) to investigate the value of serum chemokine ligand 7 (CXCL7) in diagnosis and prognosis for OCRC patients. The median concentrations of CXCL7 in non-OCRC and OCRC were both high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…PPBP is released from activated platelets and is proved to be potential novel biomarker for multiple tumors. 35 , 36 It had been demonstrated that in breast cancer, PPBP, as an important immune cytokine, was secreted by tumor monocytes and played an important role in cancer cell migration, invasion, and metastasis. After PPBP antibody was administered, the abundance of M2 macrophages in the tumor microenvironment was significantly reduced, which reduced tumor growth and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…PPBP is released from activated platelets and is proved to be potential novel biomarker for multiple tumors. 35 , 36 It had been demonstrated that in breast cancer, PPBP, as an important immune cytokine, was secreted by tumor monocytes and played an important role in cancer cell migration, invasion, and metastasis. After PPBP antibody was administered, the abundance of M2 macrophages in the tumor microenvironment was significantly reduced, which reduced tumor growth and distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have focused on CXCL7 in serum from CRC patients (30), and its potential application to prognosis of obstructive colorectal cancer (33); however, the relationship between CXCL7 and angiogenesis has not previously been evaluated. In recent years, the role of chemokines in regulating angiogenesis has been revealed in several studies (52,53), including the ability of CCL19 to suppress angiogenesis by downregulating VEGF-A expression in CRC cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…5) The patient's clinical data was relatively complete. Other terms and selection criteria for healthy participants were described in our previous study (30,33). These criteria were met by 200 patients.…”
Section: Patient Selection and Tissue Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of those only the A2M, C1QBC4BPA, CD5L, CRPIGFBP3, TF, and SerpinA1 are specific to CRC tumor samples (supplemental figure 4). An analysis of the current literature revealed that A1AT 17 , ICAM2 18 , IGF2 19 , F13A 20 , CXCL7 21 , and SHBG 22 have been previously found to be associated with colon cancer.…”
Section: Resultsmentioning
confidence: 99%